Carcass performance and quality of old Creole goats, according to slaughter time (Veterinary Science, 2020)
The objective of the present work was to study the effect of the slaughter time about some carcass features and quality of old Creole goats. The study was carried out in the arid south Central Plateau of Mendoza. 30 old Creole goats were used, which were fed on a typicalnatural grasslands of the region, without supplementation and with normal breeders’ management. The first group (GI n = 15) was slaughtered in April at the return of the summer, and the second (GII = 12) was slaughtered in October at the beginning of the regrowth of natural grassland. The results found showed that old goats slaughtered in April presented greater live weight at slaughter, higher carcass performance, greater amount of meat, better muscle: bone ratio, higher level of intramuscular fat and a similar amount of bone in both groups of goats. From the results of this study, it can be concluded that the performance and composition of slaughtered old Creole goats’ meat at the return of the summer present higher quality standards to meet demand for this type of product, and that it could be commercially exploited as a lean alternative.
Keywords: Old goats; Slaughter time; Carcass performance; Meat quality